ANTAGONIST TEST OF PSEUDOMONAD FLUORESEN WHICH WAS GROWED IN SOME TYPES OF CARBON SOURCES AGAINST BLOOD DISEASE BACTERIA - Kurnia Anggraini (Universitas Negeri Padang, 2018)
. Fluorescent pseudomonads are biocontrol agents that can control several plant diseases. Plant diseases can be caused by bacteria, fungi and nematodes. Blood Disease Bacteria (BDB) is a bacterium that causes blood disease in banana plants. Blood Disease Bacteria (BDB) disease control can be done using biocontrol agent Cas3 fluorescent pseudomonad isolates. This research is an experimental study, using a completely randomized design (CRD) with three treatments and five replications. The treatment is 1. glucose, 2. fructose and 3. glycerol. The data observed were inhibitory zones formed after testing the flourescent pseudomonad against Blood Disease Bacteria (BDB). Data were analyzed using the Analysis of Variance (ANOVA) test and continued with a DNMRT further test at the level of 5%. The results obtained are different carbon sources affecting the size of the inhibitory zone formed by the Cas3 flourescent pseudomonad against BDB. Meanwhile, the best carbon source for the growth of flourescent pseudomonads in producing a inhibitory zone against BDB.